2021
DOI: 10.21203/rs.3.rs-948407/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Network-Based Analysis of The Genetic Effects of SARS-CoV-2 Infection To Patients With Exacerbation of Virus-Induced Asthma (VAE)

Abstract: Background Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a novel RNA virus that emerged in late 2019 and was responsible for coronavirus disease (COVID-19). The WHO has declared the COVID-19 in the world pandemic. The most exacerbations of asthma are triggered by viral infections. However, the genetic effects of COVID-19 on asthma need to be further studied. Results Eighty-eight common differentially expressed genes (cDEGs) were identified in datasets GSE147507 and GSE30326. Function analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…This network pharmacology workflow has enabled us to identify some relevant drugs as candidates for drug repurposing for the treatment of COVID-19 progression based on the viral and human protein interactions observed in our networks. Some of the drugs identified in the present study have in fact been proposed as candidates for the treatment of COVID-19 by different authors, for example, 1) disulfiram, where its uses are associated with a lower risk of COVID-19 ( Fillmore et al, 2021 ); 2) auranofin, which inhibits SARS-CoV-2 replication and attenuates inflammation in human cells ( Marzo and Messori, 2020 ; Rothan et al, 2020 ); 3) suloctidil, which was recommended for the treatment of COVID-19-induced exacerbation of asthma ( Guo et al, 2021 ); and 4) gefitinib, which was reported to inhibit spike-driven fusion ( Braga et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This network pharmacology workflow has enabled us to identify some relevant drugs as candidates for drug repurposing for the treatment of COVID-19 progression based on the viral and human protein interactions observed in our networks. Some of the drugs identified in the present study have in fact been proposed as candidates for the treatment of COVID-19 by different authors, for example, 1) disulfiram, where its uses are associated with a lower risk of COVID-19 ( Fillmore et al, 2021 ); 2) auranofin, which inhibits SARS-CoV-2 replication and attenuates inflammation in human cells ( Marzo and Messori, 2020 ; Rothan et al, 2020 ); 3) suloctidil, which was recommended for the treatment of COVID-19-induced exacerbation of asthma ( Guo et al, 2021 ); and 4) gefitinib, which was reported to inhibit spike-driven fusion ( Braga et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%